2018
DOI: 10.18471/rbe.v32.24935
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Vida De Homens E Mulheres Em Hemodiálise

Abstract: Como citar este artigo: Gomes NDB, Leal NPR, Pimenta CJL, Martins KP, Ferreira GRS, Costa KNFM. Qualidade de vida de homens e mulheres em hemodiálise Rev baiana enferm. 2018;32:e24935.Objetivo: avaliar a qualidade de vida de pessoas que realizam hemodiálise. Método: estudo descritivo, transversal, com abordagem quantitativa, realizado com 40 participantes em um hospital de referência de João Pessoa, Paraíba, Brasil, entre os meses de março e abril de 2016. A coleta de dados ocorreu mediante entrevista, utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
0
5
0
18
Order By: Relevance
“…Conversely, a study conducted with women prisoners in Ceará showed different results, since the majority of the women had undergone preventive exams within the previous year. 16 The QoL scores of the detainees, overall and in the different domains, were lower than those identified in other studies [25][26][27][28][29] that used the same instrument. When comparing the results of the present study with those of studies carried out with healthy women, or even with women affected by serious illnesses, the inmates' QoL mean scores were significantly lower, demonstrating the negative impact of the prison situation on the women's lives.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Conversely, a study conducted with women prisoners in Ceará showed different results, since the majority of the women had undergone preventive exams within the previous year. 16 The QoL scores of the detainees, overall and in the different domains, were lower than those identified in other studies [25][26][27][28][29] that used the same instrument. When comparing the results of the present study with those of studies carried out with healthy women, or even with women affected by serious illnesses, the inmates' QoL mean scores were significantly lower, demonstrating the negative impact of the prison situation on the women's lives.…”
Section: Discussionmentioning
confidence: 60%
“…The mean of the overall QoL of the inmates was 46, while the mean was not lower than 55.2 in any other study, with the same trend for the domain scores. [25][26][27][28][29] Prison influenced the women's perception of their QoL, with significantly negative results for those that reported health problems and that lacked or had impaired sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Já a idade corrobora com o observado nacionalmente (1). Por sua vez, chama-se a atenção para a baixa escolaridade (11), pois pode ser um fator que contribui para a não adesão ao tratamento, como notado em um estudo realizado com hipertensos (12).…”
Section: Discussionunclassified
“…As duas maiores causas da doença renal crônica (DRC), de acordo com o censo de 2016 da Sociedade Brasileira de Nefrologia (SBN), continuam sendo o diabetes e a hipertensão arterial. Nesta pesquisa, observou-se que a maioria dos participantes apresenta diabetes e hipertensão como principais causas da DRC, o que corrobora também com outros estudos (6,18,20,22) .…”
Section: Discussionunclassified